Machine Learning approach for malware detection using executable files features extraction - Voranau, A.A.; Harakhavik, Y.V. (Штучний інтелект, 2018)
A malicious software is generally an executable program which usually settles itself in the system, replicates by copying itself, and has a malicious effect. Modern antivirus systems detect malware by knowing its pattern and detect a new virus quite difficult. There are a lot of heuristic techniques are used for detecting an unknown malware which are usually consume a lot of system memory and CPU resources. This load can be overcome by training a machine learning model which collects features from Portable Executable (PE) file which are used for identifying an unknown virus patterns. A technique to collect these features from PE file is proposed in this paper. Вредоносное ПО, как правило, представляет собой исполняемую программу, которая обычно располага-ется в системе, реплицируется путем копирования и оказывает вредоносное воздействие. Современные анти-вирусные системы обнаруживают вредоносное ПО, зная его паттерн, а обнаруживать новый вирус довольно сложно. Существует множество эвристических методов, используемых для обнаружения неизвестных вредо-носных программ, которые обычно потребляют много системной памяти и ресурсов процессора. Эту нагрузку можно преодолеть путем обучения модели машинного обучения, которая собирает данные из Portable Executable (PE) файла, которые используются для идентификации неизвестных вирусных паттернов. В данной статье предлагается метод сбора этих характеристик из PE-файла.